Corrosion of Q235 carbon steel induced by sulfate-reducing bacteria in groundwater: corrosion behavior, corrosion product, and microbial community structure - Wenxin Hua; Rui Sun; Xiaoyan Wang; Yunyun Zhang; Jiaxing Li; Ri Qiu; Yu Gao (Environmental Science and Pollution Research, 2023)

A study on the cyclic shear and particle breakage characteristics of the interface between steel and calcareous sand - Rui Wang; Jukun Guo; Shengyou Lei; Xiaowei Wang; Wentao Rong; Zhihua Yu (Marine Georesources & Geotechnology, 2023)

Using 2DVD technology to explore droplet characteristic variations of sprinkler irrigation as affected by a maize canopy - Jian Wang; Yu Xiang; Rui Chen; Hong Li (Computers and Electronics in Agriculture, 2023)

Leaf spot on cucumber caused by Stemphylium vesicarium newly reported in China - Xiaoyan Yu; Rui Han; Weiqian Zhang; Zhihua Li; Xue Zhang; Xiangjing Wang; Wensheng Xiang; Junwei Zhao (Crop Protection, 2023)

CD4 is an important host factor for Japanese encephalitis virus entry and replication in PK-15 cells - Qi Wang; Shuqing Yang; Ke Yang; Xinran Li; Yu Dai; Yi Zheng; Sanjie Cao; Qigui Yan; Xiaobo Huang; Yiping Wen; Qin Zhao; Senyan Du; et al. (Veterinary Microbiology, 2023)

The co-regulation of the gut microbiome and host genes might play essential roles in metformin gastrointestinal intolerance - Huixiang Zhang; Jiao Lai; Lihuan Zhang; Wei Zhang; Xun Liu; Qilin Gong; Hongxi Tian; Mingzhi Yang; Tao Yang; Rui Zhao; Dongqing Li; Hehua Huang; et al. (Toxicology and Applied Pharmacology, 2023)

Environmental stressors altered the groundwater microbiome and nitrogen cycling: A focus on influencing mechanisms and pathways - Jian Li; Lei Yang; Shihang Yu; Aizhong Ding; Rui Zuo; Jie Yang; Xiaofei Li; Jinsheng Wang (Science of The Total Environment, 2023)

Nitrite stimulates HONO and NOx but not N2O emissions in Chinese agricultural soils during nitrification - Yaqi Song; Dianming Wu; Xiaotang Ju; Peter Dörsch; Mengdi Wang; Ruhai Wang; Xiaotong Song; Lingling Deng; Rui Wang; Zhiwei Gao; Haroon Haider; Lijun Hou; et al. (Science of The Total Environment, 2023)

Evaluation of GPM IMERG and error sources for tropical cyclone precipitation over eastern China - Fengjiao Chen; Rui Wang; Peng Liu; Lu Yu; Yan Feng; Xiaoyi Zheng; Jinlan Gao (Journal of Hydrology, 2023)

Significant methane ebullition from large shallow eutrophic lakes of the semi-arid region of northern China - Linxiang Zhang; Xiangwei Li; Ruihong Yu; Yue Geng; Liangqi Sun; Heyang Sun; Yuan Li; Zhonghua Zhang; Xiangyu Zhang; Xue Lei; Rui Wang; Changwei Lu; et al. (Journal of Environmental Management, 2023)

pH-responsive ZIF-8 film-coated mesoporous silica nanoparticles for clean, targeted delivery of fungicide and environmental hazard reduction - Yingjian Ma; Yinmin Wang; Rui Zhao; Zhijie Wang; Shuang Li; Meng Yu; Sen Pang; Xinyu Guo; Yong Xu; Xuemin Wu (Journal of Environmental Chemical Engineering, 2023)

Highly-efficient hydrogen production from ammonia decomposition over Co-doped graphdiyne under moderate temperature - Lishan Liu; Feng Gong; Yunlong Xie; Sijun Wang; Yu Qiu; Zhihua Wang; Rui Xiao (Fuel, 2023)

Exploring metal-free ionic covalent organic framework nanosheets as efficient OER electrocatalysts via cationic-π interactions - Rui Wang; Ziqi Zhang; Jinquan Suo; Li Liao; Leibo Li; Zhuochen Yu; Heng Zhang; Valentin Valtchev; Shilun Qiu; Qianrong Fang (Chemical Engineering Journal, 2023)

Pyroptosis induction synergized with IDO inhibition of ternary biomedicine for photodynamic activated tumor immunotherapy - Ali Chen; Ni Yang; Wei Zhang; Rongrong Zheng; Rui Yu; Renjing Kong; Yuqing Wang; Hong Cheng; Xiyong Yu; Shiying Li (Chemical Engineering Journal, 2023)

Fossil samaras of Acer L. (Sapindaceae) from the Upper Pliocene of western Yunnan, southwestern China - Zhuo-Er Wang; Rui Cao; Hong Ding; Yong-Tong Huang; Zhi-Hui Song; Su-Ting Ding; Jing-Yu Wu (Palaeobiodiversity and Palaeoenvironments, 2023)

Changes in Soil Bacterial and Fungal Community Composition and Response of Functional Groups to Different Proportions of N/P/K Fertilizer Short-Term Supply in Torreya grandis Soil - Chenliang Yu; Qi Wang; Congcong Kong; Yuanyuan Guan; Yi Li; Rui Zhang; Hua Qin; Jiasheng Wu (Journal of Soil Science and Plant Nutrition, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Single-cell transcriptome analysis revealing the intratumoral heterogeneity of ccRCC and validation of MT2A in pathogenesis - Jie Wang; Zili Zuo; Zongze Yu; Zhigui Chen; Xiangdi Meng; Zhaosen Ma; Jiqiang Niu; Rui Guo; Lisa Jia Tran; Jing Zhang; Tianxiao Jiang; Fangdie Ye; et al. (Functional & Integrative Genomics, 2023)

Prevalence of Ureaplasma species among patients at a tertiary hospital in China: a 10-year retrospective study from 2013 to 2022 - Ziran Wang; Mingqi Xia; Yu Chen; Zhuo Yang; Jie Yi; Lingjun Kong; Han Zhang; Guoju Luo; Rui Li; Yaling Dou (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Tracing nitrate pollution sources of karst groundwater in water resources using environmental isotopes - Yunfeng Zhang; Dalu Yu; Di Wu; Yuhui Zhao; Zhe Zhang; Bo Li; Baohui Huang; Mingguo Wang; Junru Gao; Yuxiao Kang; Rui Liu (Carbonates and Evaporites, 2023)

Nanoplastic-Induced Biological Effects In Vivo and In Vitro: An Overview - Hongxin Xie; Xue Tian; Xiaoying Lin; Rui Chen; Saima Hameed; Liming Wang; Yong-Liang Yu; Bai Li; Yu-Feng Li (Reviews of Environmental Contamination and Toxicology, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Rapid LC-MS/MS detection of 25-hydroxyvitamin D in dried blood spots - Hai-Bo Wang; Xuan Xiao; Wen Dai; Rui Peng; Juan Le; Yu-Qi Feng; Shao-Ting Wang (Analytica Chimica Acta, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Identification and nucleotide sequencing of a novel partitivirus derived from Rhizoctonia solani AG-4 HG III isolate A14 - Rui Shi; Bengzha Dong; Qiaodi Wang; Wurong Chen; Zebin Chen; Shuhui Yu; Song Jin; Yanqiong Li (Archives of Virology, 2023)

The hepatoprotective effects of plant-based foods based on the “gut–liver axis”: a prospective review - Qiongdan Hu; Wan Liao; Zhen Zhang; Sanjun Shi; Shuguang Hou; Ningping Ji; Xinjie Zhang; Qian Zhang; Yangyang Liao; Linghui Li; Zongping Zhu; Yi Chen; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Engineering a Pseudomonas putida as living quorum quencher for biofilm formation inhibition, benzenes degradation, and environmental risk evaluation - Yi-Mei Xue; Yong-Chao Wang; Yu-Ting Lin; Guan-Yu Jiang; Rui Chen; Ruo-Lin Qin; Xiao-Qiang Jia; Can Wang (Water Research, 2023)

Subchronic exposure to di-(2-ethylhexyl) phthalate (DEHP) elicits blood–brain barrier dysfunction and neuroinflammation in male C57BL/6J mice - Wen-qiang Ren; Nuo Liu; Yan Shen; Xian-yan Wang; Qiong Zhou; Chen Rui; Xiao-han Yang; Sheng-long Cao; Ling-yu Li; Yán Wāng; Qu-nan Wang (Toxicology, 2023)

Distribution, sources, and potential health risks of fluoride, total iodine, and nitrate in rural drinking water sources of North and East China - Shier Huang; Jiaxun Guo; Yu Xie; Rui Bian; Nan Wang; Weixiao Qi; Huijuan Liu (Science of The Total Environment, 2023)

Glyphosate-based herbicide (GBH) challenged thermoregulation in lizards (Eremias argus), compensatory warming could mitigate this effect - Simin Yu; Yufan Nie; Zikang Wang; Luyao Zhang; Rui Liu; Yuping Liu; Hongjun Zhang; Wentao Zhu; Mingqi Zheng; Jinling Diao (Science of The Total Environment, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Plant and animal positive-sense single-stranded RNA viruses encode small proteins important for viral infection in their negative-sense strand - Pan Gong; Qingtang Shen; Mingzhen Zhang; Rui Qiao; Jing Jiang; Lili Su; Siwen Zhao; Shuai Fu; Yu Ma; Linhao Ge; Yaqin Wang; Rosa Lozano-Durán; et al. (Molecular Plant, 2023)

Evaluating soil water movement and soil water content uniformity under sprinkler irrigation with different soil texture and irrigation uniformity using numerical simulation - Rui Chen; Hong Li; Jian Wang; Xin Guo; Yu Xiang (Journal of Hydrology, 2023)

Unveiling the pollution and risk of atmospheric (gaseous and particulate) polycyclic aromatic hydrocarbons (PAHs) in a heavily polluted Chinese city: A multi-site observation research - Tao Wang; Luyao Zhang; Pei Zhang; Guangyuan Yu; Chong Chen; Xiaofei Qin; Guochen Wang; Xiansheng Liu; Rui Li; Liwu Zhang; Zhonghuan Xia (Journal of Cleaner Production, 2023)

Whole-genome analysis of the benzoic acid-degrading bacterium Bacillus halotolerans B28 to reveal its phytoprobiotic effects - Dandan Wang; Li Sun; Hong Yu; Chengkai Zhang; Xin Guan; Mengliang Wang; Rui Cheng; Chao Wang; Zhihong Xie (International Biodeterioration & Biodegradation, 2023)

Experimental study on enhanced coal seam gas extraction by uniform pressure/pulse pressure N2 injection - Peng-fei Ji; Hai-fei Lin; Xiang-guo Kong; Shu-gang Li; Yu-chu Cai; Rui-zhe Wang; Yu Tian; Tian-shuo Zhao (Fuel, 2023)

Strategy of functional nucleic acids-mediated isothermal amplification for detection of foodborne microbial contaminants: A review - Jie Zhou; Teng-Yu Wang; Zhi Lan; Han-Jie Yang; Xing-Jian Ye; Rui Min; Zhao-Hui Wang; Qing Huang; Jing Cao; Yu-E Gao; Wen-Long Wang; Xiu-Lan Sun; et al. (Food Research International, 2023)

Constituents of the fruits of Rubus chingii Hu and their neuroprotective effects on human neuroblastoma SH-SY5Y cells - Jingyi Wang; Xue Zhang; Jundong Yu; Jun Du; Xiaohong Wu; Liang Chen; Rui Wang; Yingchun Wu; Yiming Li (Food Research International, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Ferrostatin-1-loaded thermosensitive nanodelivery system for noise-induced hearing loss treatment - Peng-Wei Ma; Pei-Heng Lu; Hao Yuan; Jia-Wei Chen; Wei Gao; Yu-Qiang Lun; Jia-Ning Guo; Xue-Rui Ding; Rui Liang; Si-Yu Li; Zi Wang; Wei-Long Wang; et al. (Chemical Engineering Journal, 2023)

Demethylation-Driven ligase chain reaction for simultaneously sensitive detection of m6A demethylase FTO and m1A demethylase ALKBH3 in breast cancer at Single-Molecule level - Ming-hao Liu; Qian Zhang; Wan-tong Yu; Jian-Ge Qiu; Hui-min Yuan; Chuan-rui Wang; Bing-Hua Jiang; Yan Zhang; Chun-yang Zhang (Chemical Engineering Journal, 2023)

Constructing MoS2-SnS heterostructures on N-doped carbon nanosheets for enhanced catalytic conversion of polysulfides in lithium-sulfur batteries - Junpu Zhang; Wen Xi; Feng Yu; Youfang Zhang; Rui Wang; Yansheng Gong; Beibei He; Huanwen Wang; Jun Jin (Chemical Engineering Journal, 2023)

Transient, printable and recyclable gelatin hydrogels with enhanced mechanical sensing and electromagnetic shielding performance by incorporation of reduced graphene oxide - Rui Yin; Chen Zhang; Youyou Chen; Yu Wang; Qiang Feng; Yaming Liu; Minghan Yu; Yunhuan Yuan; Cheng-Yan Xu; Feihua Liu; Weiwei Zhao (Chemical Engineering Journal, 2023)

Unexpected moderate contribution of intermediate volatility organic compounds from gasoline vehicle emission to secondary organic aerosol formation in summer of Beijing - Rongzhi Tang; Song Guo; Quanyang Lu; Kai Song; Yuanzheng Gong; Rui Tan; Kefan Liu; Hui Wang; Ying Yu; Ruizhe Shen; Shiyi Chen; Limin Zeng; et al. (Atmospheric Research, 2023)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

Reduced attention on restricted organochlorine pesticides, whereas still noteworthy of the impact on the deep soil and groundwater: a historical site study in southern China - Changlin Xu; Yue Cai; Rui Wang; Jing Wu; Guoyi Yang; Yahui Lv; Dehong Liu; Yu Deng; Yaqi Zhu; Qing Zhang; Lijun Wang; Shengwei Zhang (Environmental Geochemistry and Health, 2023)

A new anchor-siphon drainage combined method used for slope stabilization - Hong-yue Sun; Xu Wang; Yang Yu; Jun-wei Shu; Tian-long Wang; Rui Luo; Zhao-wei Chu (Journal of Mountain Science, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Multiphase wavefield inversion methodology for seismic analysis of soil-structure interaction systems - Gang Li; Yaohui Xue; Rui Wang; Han Zhang; Zhiqian Dong; Dinghao Yu (Soil Dynamics and Earthquake Engineering, 2023)

A superstable, flexible, and scalable nanofluidic ion regulation composite membrane - Lianmeng Si; Yihan Wu; Hong Xiao; Wensi Xing; Rui Song; Yiju Li; Sha Wang; Xu Liang; Wenshan Yu; Jianwei Song; Shengping Shen (Science Bulletin, 2023)

Neolignan derivatives from Penthorum chinense with antitumor activity in human colorectal cancer cells by regulating Wnt/β-catenin signaling pathway - Mengqi Lu; Jingya Ruan; Rui Yu; Ying Zhang; Wei Zhao; Dingshan Yang; Wanxia Wang; Yi Zhang; Tao Wang (Phytochemistry, 2023)

Triterpenoid saponins from Psammosilene tunicoides and their antinociceptive activities - Yan-Hong Li; Xi-Shan Bai; Xiu-Xia Yang; Yu-Xiao Li; Hong-Rui Li; Zi-Liang Wang; Wei Wang; Kai Tian; Xiang-Zhong Huang (Phytochemistry, 2023)

Reducing transport resistance in highly concentrated fine-grained slurry pipelines by vibration-induced fluidization - Minxi Zhang; Yangliuer Chen; Mingzhi Li; Rui Wang; Guoliang Yu (Ocean Engineering, 2023)

Direct immobilization of Se(IV) from acidic Se(IV)-rich wastewater via ferric selenite Co-precipitation - Zidan Yuan; Rui Su; Xu Ma; Le Yu; Yuanming Pan; Ning Chen; Roman Chernikov; Leo Ka Long Cheung; Reza Deevsalar; Ayetullah Tunc; Liang Wang; Xiangfeng Zeng; et al. (Journal of Hazardous Materials, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Sulfur-decorated Fe/C composite synthesized from MIL-88A(Fe) for peroxymonosulfate activation towards tetracycline degradation: Multiple active sites and non-radical pathway dominated mechanism - Jin Qian; Yichu Zhang; Zhijie Chen; Ran Yu; Yin Ye; Rui Ma; Kailong Li; Lingzhen Wang; Dongqi Wang; Bing-Jie Ni (Journal of Environmental Management, 2023)

Chloride removal from sewage using bismuth trioxide: Characterization and optimization by response surface methodology (RSM) - Liangjing Zhang; Yu Wang; Yunlong Liu; Shucong Lv; Rui Wang; Xiaokun Hu; Yuchen Liu; Zhaojun Dong; Kuixuan Lin; Lusan Liu (Journal of Environmental Chemical Engineering, 2023)

Boosting PFOA photocatalytic removal from water using highly adsorptive and sunlight-responsive ZIF67/MIL-100(Fe) modified C3N4 - Peidong Su; Chunhui Zhang; Yu Liu; Junke Zhang; Ridha Djellabi; Rui Wang; Junqiang Guo; Rui Zhang; Hongwei Guo; Xiang Ding; Xinyue Liu (Journal of Environmental Chemical Engineering, 2023)

Evaluating the impact of the humic acid amendment on antibiotic resistance genes reduction and product quality during swine manure composting - Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Shan-Shan Sun; Xi Yang; Yu-Sen Luo; Ayodeji Bello; Taha Ahmed Mohamed; Rong-Jie Ren; Wan-Ting Li; Rashid Mohamed Ahmed; Rui-Long Wang (Journal of Environmental Chemical Engineering, 2023)

Enhanced encapsulation of lutein using soy protein isolate nanoparticles prepared by pulsed electric field and pH shifting treatment - Rui Wang; Man-Qin Zeng; Yu-Wei Wu; Yong-Xin Teng; Lang-Hong Wang; Jian Li; Fei-Yue Xu; Bo-Ru Chen; Zhong Han; Xin-An Zeng (Food Chemistry, 2023)

The active synergetic microbiota with Aspergillus as the core dominates the metabolic network of ester synthesis in medium-high temperature Daqu - Yan Wang; Shikai Quan; Yajiao Zhao; Yu Xia; Rui Zhang; Maofang Ran; Zhengyun Wu; Wenxue Zhang (Food Microbiology, 2023)

Trade-offs and synergies of plant traits co-drive efficient nitrogen use in intercropping systems - Hao Yang; Wei-Ping Zhang; Hua-Sen Xu; Rui-Peng Yu; Ye Su; Surigaoge Surigaoge; Pei-Xuan Wang; Xin Yang; Hans Lambers; Long Li (Field Crops Research, 2023)

Leaf senescence, nitrogen remobilization, and productivity of maize in two semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Fei Mo; Aziz Khan; Asfa Batool; Wei Zhang; Jun-Sheng Lu; Ying Zhu; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; et al. (European Journal of Agronomy, 2023)

Epoxy-based high-k composite vitrimer: With low dielectric loss, high breakdown strength and surface electrical damage repairability - Yu-Cheng Zhang; Wen-Dong Li; Xin Zhao; Fan-Bo Meng; Peng Sun; Chao Wang; Guang-Zhi Guo; Wen-Rui Li; Guan-Jun Zhang (Chemical Engineering Journal, 2023)

Astragaloside IV-mediated inhibition of oxidative stress by upregulation of ghrelin in type 2 diabetes–induced cognitive impairment - Rui-hua Zhang; Shan-shan Cao; Yong Shi; Xin Wang; Lei-lei Shi; Yu-han Zhang; Chao-jun Han; Bin Wang; Liang Feng; Ji-ping Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

An epoxide-based covalent sensor to detect cardiac proteome aggregation in a cardio-oncology model - Hao Jin; Di Shen; Biao Jing; Zhenduo Zhang; Zhiming Wang; Rui Sun; Huaiyue Zhang; Jialu Sun; Haochen Lyu; Yu Liu; Lili Wang (Analytica Chimica Acta, 2023)

Complete Genome Sequence of Streptomyces sp. HP-A2021, a Promising Bacterium for Natural Product Discovery - Lan-Fang Li; Qing-Xuan Wu; Hao Wu; Yao Li; Qian Peng; Ren-Hao Han; Da-Hu Zhang; Wei-Dong Yu; Rui Xu; Juan Wang; Zhaobin Fan; Shao-Yang Hou (Biochemical Genetics, 2023)

Comparative transcriptome profiling reveals RNA splicing alterations and biological function in patients exposed to occupational noise - Jia-Wei Chen; Jun-Jie Shao; Shao-Fei Zhao; Pei-Heng Lu; Si-Yu Li; Hao Yuan; Peng-Wei Ma; Yu-Qiang Lun; Wei-Long Wang; Rui Liang; Wei Gao; Qian Yang; et al. (Environmental Science and Pollution Research, 2023)

Megastigmane sesquiterpenoids from Saussurea medusa and their anti-inflammatory activities - Jing-Ya Cao; Qi Dong; Zhi-Yao Wang; Ye Zhao; Yu Ren; Li-Juan Mei; Yan-duo Tao; Rui-Tao Yu (Natural Product Research, 2023)

Carbon source shaped microbial ecology, metabolism and performance in denitrification systems - Yuan Pan; Rui-Zhe Sun; Yan Wang; Guan-Lin Chen; Ying-Ying Fu; Han-Qing Yu (Water Research, 2023)

The enantioselective environmental fate of mandipropamid in water-sediment microcosms: Distribution, degradation, degradation pathways and toxicity assessment - Jing Zhang; Yanhong Li; Yuting Tan; Yu Zhang; Rui Li; Liangliang Zhou; Minghua Wang (Science of The Total Environment, 2023)

Identification of priority pollutants and key factors affecting environmental risks of lead‑zinc mine tailing sites - Jing-yu Peng; Shuai Zhang; Yu-jing Wang; Rui-feng Zhao; Yi-ling Zhou; Jian-wei Zhou (Science of The Total Environment, 2023)

Properties of dolomitizing fluids indicated by rare earth elements: A case study of the Upper Miocene to Pliocene dolostone on the Xisha Islands, South China Sea - Ruoxia Shen; Anjiang Shen; Kefu Yu; Cole A. McCormick; Wei Jiang; Yang Xiao; Lü Wu; Rui Wang (Sedimentary Geology, 2023)

Nitrate attenuation with rising groundwater levels: An integrated assessment using isotope tracers and microbial signatures - Jie Li; Yulian Liu; Wei Dai; Jian Li; Pingheng Yang; Lijun Tian; Shihang Yu; Rui Zuo; Yuanzheng Zhai; Wei Song; Fan Yang; Ruijing Zhou; et al. (Journal of Hydrology, 2023)

Trade-off strategy for the usage of thiencarbazone-methyl·isoxaflutole on maize fields: Nitrogen-associated microbial response and environmental implications - Yonglu Wang; Fengsong Zhang; Lida Wang; Huajun Fang; Guixiang Zhang; Xiumei Zhao; Siyi Liu; Qingchao Li; Yue Liu; Rui Ren; Yu An; Lisha Fan (Journal of Cleaner Production, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Comprehensive understanding of tetracycline hydrochloride adsorption mechanism onto biochar-based gel pellets based on the combination of characterization-based and approximate site energy distribution methods - Bai-Qin Zhou; Qian-Qian Sang; Yu-Jun Wang; Hui Huang; Fang-Jun Wang; Rui-Chun Yang; Yuan-Tian Zhao; Zi-Jie Xiao; Chun-Yue Zhang; Hui-Ping Li (Journal of Cleaner Production, 2023)

GRPR down-regulation inhibits spermatogenesis through Ca2+ mediated by PLCβ/IP3R signaling pathway in long-term formaldehyde-exposed rats - Yan-qi Yang; Rui-fang Sun; Pan Ge; Wen-Xing Li; Xiang Zhang; Jian Zhang; Lu Ye; Nan Zhang; Si-yu Wang; Mo-qi Lv; Dang-xia Zhou (Food and Chemical Toxicology, 2023)

Controllable micro cross-linking towards multifunctional flame-retardant aliphatic polyamide - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Qing-Song Liu; Min Jiang; De-Ming Guo; Hai-Bo Zhao; Wen-Da Li; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Insights on rational design and regulation strategies of Prussian blue analogues and their derivatives towards high-performance electrocatalysts - Yu-Rui Ji; Ya-Fei Guo; Xu Liu; Peng-Fei Wang; Ting-Feng Yi (Chemical Engineering Journal, 2023)

Numeric and nonnumeric information input to predict adsorption amount, capacity and kinetics of tetracyclines by biochar via machine learning - Bai-Qin Zhou; Rui-Chun Yang; Hui-Ping LI; Yu-Jun Wang; Chun-Yue Zhang; Zi-Jie Xiao; Zhong-Qi He; Wei-Hai Pang (Chemical Engineering Journal, 2023)

An anaerobic dynamic membrane bioreactor (AnDMBR) system enhanced the biogas conversion efficiency and stability of mesophilic codigestion with waste activated sludge and food waste - Bao-Shan Xing; Yi Zhang; Rui-Qi Zhang; Jing Ma; Xiang-Lin Chang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Chemical Engineering Journal, 2023)

Microbial metabolism and humic acid formation in response to enhanced copper and zinc passivation during composting of wine grape pomace and pig manure - Yingchao Zhang; Yang Xu; Xinlong Yu; Jinkang Li; Guang Chen; Shuaijie Wang; Yanping Xu; Rui Xu; Baohai Zhang; Hongqiong Zhang (Bioresource Technology, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Punicalagin relieves lipotoxic injuries on pancreatic β-cells via regulating the oxidative stress and endoplasmic reticulum stress-mediated apoptosis - Ning Wang; Kexin Yang; Jun Wang; Jinghe Liang; Shengbo Yu; Aiqing Zhu; Rui Zhang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Phylogenetic analysis and molecular characterization of the co-infection of the new variant of the porcine epidemic diarrhea virus and the novel porcine kobuvirus isolated from piglets with diarrhea - Ran Wei; Rui Shang; Kaihui Cheng; Song Wang; Xiaoyuan Yuan; Jiaqiang Wu; Zhijun Yu (Brazilian Journal of Microbiology, 2023)

Transient analyses for China initiative Accelerator Driven System using the extended BELLA code - Guan Wang; Janne Wallenius; Rui Yu; Wei Jiang; Lu Zhang; Xin Sheng; Di Yun; Long Gu (Annals of Nuclear Energy, 2023)

Fast and bioluminescent detection of antibiotic contaminants by on-demand transcription of RNA scaffold arrays - Rui Zhang; Yu Wang; Haifeng Deng; Shiwen Zhou; Yunhua Wu; Yong Li (Analytica Chimica Acta, 2023)

Daily runoff prediction based on the adaptive fourier decomposition method and multiscale temporal convolutional network - Lijin Yu; Zheng Wang; Rui Dai; Wanliang Wang (Environmental Science and Pollution Research, 2023)

Epicoccum sorghinum as leaf spot disease-causing pathogen in ginger (Zingiber officinale Rosc.) in China - Xiaoyan Yu; Zhihua Li; Rui Han; Weiqian Zhang; Jing Zhang; Weiyue Cao; Yue Ma; Xiangjing Wang; Junwei Zhao; Wensheng Xiang (Crop Protection, 2023)

Nano-pesticide carrier O-Carboxymethyl chitosan is indigestible in Apis cerana cerana and affects intestinal flora - Sheng-nan Li; Hao Wu; Rui-quan Hou; Jing-tong Zhou; Su-kun Lin; Kun-yu Zhao; Rui-fei Wang; Su-qing Huang; Zhi-xiang Zhang (Science of The Total Environment, 2023)

Dynamic probabilistic risk assessment of emergency response for intelligent coal mining face system, case study: Gas overrun scenario - Yan Zhang; Yu-Hao Wang; Xu Zhao; Rui-Peng Tong (Resources Policy, 2023)

Experimental study on the influence of a T-foil and bulbous bow on the resistance and motion in regular head waves of trimarans - Rui Deng; Sichong Huang; Shigang Wang; Hailong Liu; Xiang Yu; Tiecheng Wu (Ocean Engineering, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Mapping submarine landslides susceptibility in continental slopes with rich gas hydrates - Lin Tan; Fang Liu; Yu Huang; Rui Wang; Jianhua Geng; Giovanni Crosta; Paolo Frattini (Gas Science and Engineering, 2023)

Enlocking the high Zn2+-storage of conversion-type Te cathode by regulating the surface binding-interaction with graphene - Cong Guo; Shangjun Yi; Rui Si; Yixiao Wang; He Liu; Feng Yu; Jingfa Li (Chemical Engineering Journal, 2023)

Ratiometric SERS imaging for indication of peroxynitrite fluctuations in diabetic wound healing process - Hui Chen; Shanshan Lin; Dianqi Zhang; Yanlong Xing; Fabiao Yu; Rui Wang (Chemical Engineering Journal, 2023)

Will the southward center of gravity migration of population, floor area, and building energy consumption facilitate building carbon emission reduction in China? - Rui Li; Kairui You; Weiguang Cai; Jiebing Wang; Yuan Liu; Yanhui Yu (Building and Environment, 2023)

Assessment of Chloride Salt Release Flux from Fluidized Cohesive Sediments in Quiescent Water - Jing Yuan; Binghui Zheng; Rui Wang; Minxi Zhang; Guoliang Yu (Water, Air, & Soil Pollution, 2023)

A spike-trimer protein-based tetravalent COVID-19 vaccine elicits enhanced breadth of neutralization against SARS-CoV-2 Omicron subvariants and other variants - Rui Wang; Hongpeng Huang; Chulin Yu; Chunyun Sun; Juan Ma; Desheng Kong; Yalong Lin; Dandan Zhao; Shaozheng Zhou; Jianbo Lu; Sai Cao; Yanjing Zhang; et al. (Science China Life Sciences, 2023)

LncRNA BBOX1-AS1 Contributes to the Progression of Esophageal Carcinoma by Targeting the miR-361-3p/COL5A1 Axis - Yu-Hai Lu; Dong-Sheng He; Ying Li; Hong Wang; Rui-Dong Ma (Biochemical Genetics, 2023)

High prevalence of vitamin D deficiency in Asia: A systematic review and meta-analysis - Zhiwei Jiang; Rui Pu; Na Li; Chaozhen Chen; Jialu Li; Wei Dai; Yuchen Wang; Jinxing Hu; Danji Zhu; Qiong Yu; Yuan Shi; Guoli Yang (Critical Reviews in Food Science and Nutrition, 2023)

Screening eco-friendliness tire antioxidants alternatives: functional 2,2,4-trimethyl-1,2-dihydroquinoline derivatives design and toxicity evaluation - Yu Wang; Rui Fu; Peixuan Sun; Xinao Li; Wenjin Zhao (Environmental Science and Pollution Research, 2023)

A method establishment and application for biofilm quorum quenching activity assay - Zhen Tong; Yong-Chao Wang; Guan-Yu Jiang; Xu-Rui Hu; Yi-Mei Xue; Can Wang (Chemosphere, 2023)

Investigation of the settlement mechanism and control measures of a super-large section tunnel in a giant karst cave using ultra-thick backfill method - Yuchao Zheng; Jianxiong Yan; Rui Su; Shuqi Ma; Yu Li; Xun Wang; Jieyuan Zheng; Yong Zhu; Yu Yu (Tunnelling and Underground Space Technology, 2023)

Regional CO2 accounting and market layout of incinerator fly ash management in China - Yunqi Zhai; Fang Liu; Yifan Hu; Lei Wang; Xuebin Lu; Zhihao Yu; Hanqiao Liu; Rui Zhang (Science of The Total Environment, 2023)

Innovative screening for functional improved aromatic amine derivatives: Toxicokinetics, free radical oxidation pathway and carcinogenic adverse outcome pathway - Yajing Liu; Xinao Li; Qikun Pu; Rui Fu; Zhonghe Wang; Yu Li; Xixi Li (Journal of Hazardous Materials, 2023)

Seasonal associations between air pollutants and influenza in 10 cities of southern China - Rui Zhang; Yonghong Li; Peng Bi; Siyuan Wu; Zhibin Peng; Yujie Meng; Yu Wang; Songwang Wang; Yushu Huang; Juan Liang; Jing Wu (International Journal of Hygiene and Environmental Health, 2023)

Insights into dissolved organics in non-urban areas - Optical properties and sources - Feng Yu; Xiaofei Li; Rui Zhang; Jingning Guo; Wen Yang; Lekhendra Tripathee; Lang Liu; Yuqin Wang; Shichang Kang; Junji Cao (Environmental Pollution, 2023)

Astrochronology and sedimentary noise modeling of Pliensbachian (Early Jurassic) sea-level changes, Paris Basin, France - Rui Zhang; David B. Kemp; Nicolas Thibault; Mads E. Jelby; Mingsong Li; Chunju Huang; Yu Sui; Zhixiang Wang; Dongyang Liu; Shizhen Jia (Earth and Planetary Science Letters, 2023)

Stable β-form zinc phthalocyanine cathodes for flexible Zn-ion hybrid supercapacitors with ultra-long cycling life - Daotong Han; Wenyun Wang; Shangjing Yu; Wentao Qi; Rui Ling; Chao Yang; Guangqiang Liu (Chemical Engineering Journal, 2023)

A novel fluorescent probe for imaging endogenous hydrogen sulfide in living cells and mice models of acute liver injury - Kai Wang; Rui Guo; Xu-Yang Chen; Xiu-Lin Li; Zhi-Gang Hu; Xiao Wang; Chao-Yue Wang; Ya-Juan Qin; Kun Yao; Yu-Shun Yang (Chemical Engineering Journal, 2023)

In situ polymerization of polypyrrole in oil body for efficient solar-driven freshwater collection - Hongxiang Liu; Tianshu Zou; Xingyu Cui; Miao Ding; Biao Zhang; Xiaodong Yang; Yu Han; Shuwei Nie; Yuan Zhang; Enze Wang; Lili Wang; Yan Cheng; et al. (Chemical Engineering Journal, 2023)

Late Pleistocene zinc isotopic indices of paleoproductivity variations in the tropical West Pacific - Wenlong Pei; Jiayue Wang; Xinling Wang; Liang Du; Yipeng Wang; Yujin Fan; Rui Zhang; Tiegang Li; James Russell; Fan Zhang; Xiaoxiao Yu; Zhiyong Liu; et al. (CATENA, 2023)

Potential thyroid hormone disorder risks of tire antioxidants to aquatic food chain organisms after absorbing free radicals in marine and freshwater environments - Yu Wang; Rui Fu; Xinao Li; Wenjin Zhao; Miao Liu; Yu Li (Aquatic Toxicology, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Whole-plant foods and their macromolecules: untapped approaches to modulate neuroinflammation in Alzheimer’s disease - Rui Huang; Zhenjun Zhu; Qingping Wu; Alaa El-Din Ahmed Bekhit; Shujian Wu; Mengfei Chen; Juan Wang; Yu Ding (Critical Reviews in Food Science and Nutrition, 2023)

Maternal 25(OH)D attenuates the relationship between ambient air pollution during pregnancy and fetal hyperinsulinism - Peng Wang; Wan-jun Yin; Ying Zhang; Xiao-min Jiang; Xiao-guang Yin; Yu-bo Ma; Fang-biao Tao; Rui-xue Tao; Peng Zhu (Chemosphere, 2023)

The combined effects of atrazine and warming on environmental adaptability in lizards (Eremias argus) from the perspective of a life-history traits trade-off: Gender differences in trade-off strategies may reverse mortality risk - Yufan Nie; Zikang Wang; Simin Yu; Luyao Zhang; Rui Liu; Yuping Liu; Wentao Zhu; Zhiqiang Zhou; Jinling Diao (Science of The Total Environment, 2023)

The discovery of 3-fluoroalkyl indoles as potential antifungal agents to control tomato gray mold caused by Botrytis cinerea - Rui Feng; Fei Liu; Yan Wang; Shu Xu; Wuzhang Liu; Siwei Qiao; Songtao Liu; Yu Chen; Xu Feng; Qizhi Wang; Weidong Rao (Phytochemistry Letters, 2023)

Lithospheric controls on the formation of the Qilian Shan plateau: Evidence from apatite (U Th)/He and cosmogenic 21Ne results in the Central Qilian Shan - Yan Ma; Jianzhang Pang; Dewen Zheng; Huiping Zhang; Jingxing Yu; Chaopeng Li; Rui Zhang; Yuqi Hao; Ying Wang; Ying Wu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Nanoencapsulation-based fabrication of eco-friendly pH-responsive pyraclostrobin formulations with enhanced photostability and adhesion to leaves - Yingjian Ma; Linjie Li; Rui Zhao; Zhe Sun; Yinmin Wang; Meng Yu; Shouhe Pan; Xinyu Guo; Yong Xu; Hongmei Wang; Ping Wang; Xuemin Wu (Journal of Environmental Chemical Engineering, 2023)

Degradation of aflatoxins in apple juice by pulsed light and the analysis of their degradation products - Lige Qi; Yali Ma; Rui Cai; Yu Li; Ruinan Wang; Tianli Yue; Yahong Yuan; Zhenpeng Gao; Zhouli Wang (Food Control, 2023)

Excited-state intramolecular proton transfer emitter for efficient violet-blue organic light-emitting diodes with hybridized local/charge transfer channel - Yibing Wu; Rongxin Wang; Rui Lin; Xuee Xu; Xingye Zhang; Osamah Alsalman; Yu Qiu; Ashraf Uddin; Xinhua Ouyang (Chemical Engineering Journal, 2023)

Simultaneously mapping loci related to two plant architecture traits by phenotypic recombination BSA/BSR in peanut (Arachis hypogaea L.) - Xiaona Yu; Yaoyao Li; Xinyuan Cui; Xianheng Wang; Jihua Li; Rui Guo; Fanzhuang Yan; Shaojing Zhang; Ruihua Zhao; Danlei Song; Tong Si; Xiaoxia Zou; et al. (Theoretical and Applied Genetics, 2023)

A deep learning nomogram of continuous glucose monitoring data for the risk prediction of diabetic retinopathy in type 2 diabetes - Rui Tao; Xia Yu; Jingyi Lu; Yaxin Wang; Wei Lu; Zhanhu Zhang; Hongru Li; Jian Zhou (Physical and Engineering Sciences in Medicine, 2023)

A joint application of semi-airborne and in-tunnel geophysical survey in complex limestone geology - Rui Liu; Huaifeng Sun; Dong Liu; Xiaoming Wang; Xiaosheng Zhou; Yu Zhao; Xinyu Zhao; Yang Yang; Guang Yang; Hanwu Sun (Bulletin of Engineering Geology and the Environment, 2023)

A novel recombinant porcine sapovirus infection in piglets with diarrhea in Shandong Province, China, 2022 - Ran Wei; Rui Shang; Kaihui Cheng; Song Wang; Jiaqiang Wu; Zhijun Yu (Brazilian Journal of Microbiology, 2023)

Internet addiction-induced brain structure and function alterations: a systematic review and meta-analysis of voxel-based morphometry and resting-state functional connectivity studies - Jing-Ting Sun; Bo Hu; Tian-Qi Chen; Zhu-Hong Chen; Yu-Xuan Shang; Yu-Ting Li; Rui Wang; Wen Wang (Brain Imaging and Behavior, 2023)

Diffusion mechanism of deep shale gas and its carbon isotope fractionation: a combined simulated and mathematical analysis - Yu Zou; Guojian Wang; Cheng Tao; Rui Zhou; Shangqing Zhang; Dongna Liu; Xiaohui Lin; Xuying Zheng (Geosciences Journal, 2023)

Ocean acidification altered microbial functional potential in the Arctic Ocean - Yu Wang; Rui Zhang; Yunfeng Yang; Qichao Tu; Jizhong Zhou; Nianzhi Jiao (Limnology and Oceanography, 2023)
Ocean acidification (OA) has considerably changed the metabolism and structure of plankton communities in the ocean. Evaluation of the response of the marine bacterioplankton community to OA is critical for understanding the future direction of bacterioplankton‐mediated biogeochemical processes in the ocean. Understanding the diversity of functional genes is important for linking the microbial community to ecological and biogeochemical processes. However, the influence of OA on the functional diversity of bacterioplankton remains unclear. Using high‐throughput functional gene microarray technology (GeoChip 4), we investigated the functional gene structure and diversity of bacterioplankton under three different p CO 2 levels (control: 175 μ atm, medium: 675 μ atm, and high: 1085 μ atm) in a large Arctic Ocean mesocosm experiment. We observed a higher evenness of microbial functional genes under elevated p CO 2 compared with under low p CO 2 . OA induced a more stable community as evaluated by decreased dissimilarity of functional gene structure with increased p CO 2 . Molecular ecological networks under elevated p CO 2 became more complex and stable, supporting the central ecological tenet that complexity begets stability. In particular, increased average abundances were found under elevated p CO 2 for many genes involved in key metabolic processes, including carbon degradation, methane oxidization, nitrogen fixation, dissimilatory nitrite/nitrate reduction, and sulfide reduction processes. Altogether, these results indicate a significant influence of OA on the metabolism potential of bacterioplankton in the Arctic Ocean. Consequently, our study suggests that biogeochemical cycling mediated by these microbes may be altered by the OA in the future.

2,4-Dinitrotoluene (2,4-DNT) exposure induces liver developmental damage and perturbs lipid metabolism and oxygen transport gene expression in zebrafish (Danio rerio) - Liangxia Su; Hang Sha; Jun Liu; Le Yu; Huanhuan Li; Rui Wang (Environmental Science and Pollution Research, 2023)

ZNRF2 as an oncogene is transcriptionally regulated by CREB1 in breast cancer models - Jin-Tao Liu; Zhen-Xuan Sun; Rui Zhong; Yi-Dan Zhang; Teng Wang; Yu-Dong Hou; Jian-Heng Bao; Lei Zhang; Bo Chen (Human Cell, 2023)

Effects of polystyrene nanoplastic gestational exposure on mice - Xiaoke Wang; Zixuan Zhao; Xin Wang; Wenxuan Hu; Chao luo; Xiuyu Chu; Muzhou Qian; Rui Wang; Shali Yu; Qiyun Wu; Juan Tang; Xinyuan Zhao (Chemosphere, 2023)

Underestimation of biomass burning contribution to PM2.5 due to its chemical degradation based on hourly measurements of organic tracers: A case study in the Yangtze River Delta (YRD) region, China - Qing Li; Kun Zhang; Rui Li; Liumei Yang; Yanan Yi; Zhiqiang Liu; Xiaojuan Zhang; Jialiang Feng; Qiongqiong Wang; Wu Wang; Ling Huang; Yangjun Wang; et al. (Science of The Total Environment, 2023)

Driving forces and variation in water footprint before and after the COVID-19 lockdown in Fujian Province of China - Fan Yu; Yuan Wang; Xin Liu; Jinru Yu; Dandan Zhao; Haijun Deng; Bin Guo; Rui Shi; Bowei Wu; Huayang Chen (Journal of Cleaner Production, 2023)

Preparation of a novel metal-free polypyrrole-red phosphorus adsorbent for efficient removal of Cr(VI) from aqueous solution - Longyu Qiu; Yingjun Wang; Rui Sui; Chenxi Zhu; Weiwei Yang; Yongsheng Yu; Jiaming Li (Environmental Research, 2023)

Seismic damage characteristics and evaluation of aboveground-underground coupled structures - Gang Li; Han Zhang; Rui Wang; Zhi-Qian Dong; Ding-Hao Yu (Engineering Structures, 2023)

Manipulating electron redistribution of active sites by in situ engineering B-S-V bond in VS2 catalyst for stable nitrogen fixation - Xinyue Chi; Rui Zhao; Xiaoxuan Wang; Yuanyuan Xiong; Kaixin Zhang; Zhenzhen Fu; Yebo Yao; Shuyuan Li; Zhi-Yu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Increased hypertension risk for the elderly with high blood levels of strontium and lead - Jiebao Zhang; Chunfang Xu; Yan Guo; Xingyi Jin; Zi Cheng; Qi Tao; Lin Liu; Rui Zhan; Xuemin Yu; Hongjuan Cao; Fangbiao Tao; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

A20 ameliorates disc degeneration by suppressing mTOR/BNIP3 axis-mediated mitophagy - Xin Peng; Cong Zhang; Jia-Wei Gao; Feng Wang; Jun-Ping Bao; Zhi-Min Zhou; Rui Sun; Hang-Yu Ji; Cabral VLF; Xiao-Tao Wu (Genes & Genomics, 2023)

Study on mutual harmless treatment of electrolytic manganese residue and red mud - Jing Zhang; Rui Li; Yu Zhang; Weilong He; Junjie Yang; Yu Wang (Environmental Science and Pollution Research, 2023)

Abundance and characteristics of microplastics in the Wanquan River estuary, Hainan Island - Tuan-Tuan Wang; Wang-Qing Tang; Dong-Hai Wu; Xin-Rui Yu; Guang-Yu Wang; Xing-Wei Cai; Shuai Shao; Sai Wang; Ling Mo; You-Sheng Liu; Guang-Guo Ying; Zhong-Bing Chen (Marine Pollution Bulletin, 2023)

Aggregation and construction mechanisms of microbial extracellular polymeric substances with the presence of different multivalent cations: Molecular dynamic simulation and experimental verification - Sainan Peng; Zhiyue Wang; Pingfeng Yu; Guiying Liao; Rui Liu; Dongsheng Wang; Weijun Zhang (Water Research, 2023)

mRNA 3ʹ -UTR-mediate translational control through PAS and CPE in sheep oocyte - Chun-Ru Song; Ru-Jing Zhang; Fang-Rui Xue; Xiao-Jie Zhang; Xing-Yue Wang; Dui Sun; Kang Ding; Qi Yang; Xin-Yu Wang; Cheng-Guang Liang (Theriogenology, 2023)

A semi-analytical method for predicting train-induced vibrations considering train-track-soil and soil-pile-building dynamic interactions - Zi-Yu Tao; Chao Zou; Guang-Rui Yang; Yi-Min Wang (Soil Dynamics and Earthquake Engineering, 2023)

JA-induced TaMPK6 enhanced the freeze tolerance of Arabidopsis thaliana through regulation of ICE-CBF-COR module and antioxidant enzyme system - Meng-Meng Yu; Rui Wang; Jing-Qiu Xia; Chang Li; Qing-Hua Xu; Jing Cang; Yu-Ying Wang; Da Zhang (Plant Science, 2023)

Introduction of multilayered magnetic core–dual shell SERS tags into lateral flow immunoassay: A highly stable and sensitive method for the simultaneous detection of multiple veterinary drugs in complex samples - Jian Tu; Ting Wu; Qing Yu; Jiaxuan Li; Shuai Zheng; Kezong Qi; Guohui Sun; Rui Xiao; Chongwen Wang (Journal of Hazardous Materials, 2023)

An overview on constructed wetland-microbial fuel cell: Greenhouse gases emissions and extracellular electron transfer - Liangjing Zhang; Yunlong Liu; Shucong Lv; Rui Wang; Yu Wang; Kuixuan Lin; Xiaokun Hu; Yuchen Liu; Zhaojun Dong; Lusan Liu (Journal of Environmental Chemical Engineering, 2023)

Amorphous nanophosphates of dual-metal (Co and Ni) for the decomposition of ozone under humid conditions - Qian Zhang; Jifei Liao; Guangzhi Du; Yu Lin; Xiaoqiong Liu; Rui Wang; Lingyu Huang; Wenyan Xiao; Jiahao Chen; Yan Fu (Journal of Environmental Chemical Engineering, 2023)

Formation of ferritin-agaro oligosaccharide-epigallocatechin gallate nanoparticle induced by CHAPS and partitioned by the ferritin shell with enhanced delivery efficiency - Rui Yang; Junrui Ma; Jiangnan Hu; Haili Sun; Yu Han; Demei Meng; Zhiwei Wang; Lei Cheng (Food Hydrocolloids, 2023)

A pH/cellulase dual stimuli-responsive cellulose-coated metal–organic framework for eco-friendly fungicide delivery - Yingjian Ma; Meng Yu; Yinmin Wang; Shouhe Pan; Xuelin Sun; Rui Zhao; Zhe Sun; Rui Gao; Xinyu Guo; Yong Xu; Xuemin Wu (Chemical Engineering Journal, 2023)

Boosting photocatalytic ammonia synthesis performance over OVs-Rich Ru/W18O49: Insights into the roles of oxygen vacancies in enhanced hydrogen spillover effect - Lulu Zhang; Rui Li; Luyao Cui; Zijun Sun; Lijun Guo; Xiaochao Zhang; Yunfang Wang; Yawen Wang; Zhuobin Yu; Tao Lei; Xuan Jian; Xiaoming Gao; et al. (Chemical Engineering Journal, 2023)

New insights into photochemical initial concentrations of VOCs and their source implications - Bowei Li; Shaocai Yu; Min Shao; Xinhe Li; Steven Sai Hang Ho; Xiaoyi Hu; Hongli Wang; Rui Feng; Xuekun Fang (Atmospheric Environment, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Changes in the Microbiota and their Roles in Patients with Type 2 Diabetes Mellitus - Qiao-ling He; Hui-chao Wang; Yu-ke Ma; Rui-lin Yang; Zhi-feng Dai; Jing-nan Yang; Yao Xu; Dan-dan Wei; Li-ping Zhu; Xu-hong Lin (Current Microbiology, 2023)

Highly efficient aerobic oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid over halloysite nanotubes-templated nitrogen-doped carbon supported bimetallic AuPd catalyst - Fang Wang; Changhao Yan; Rui Jiang; Yao Chen; Yanan Wei; Yu Cao; Wen Guan; Pengwei Huo; Yunlei Zhang (Applied Clay Science, 2023)

Immediate and long-term changes in the epidemiology, infection spectrum, and clinical characteristics of viral and bacterial respiratory infections in Western China after the COVID-19 outbreak: a modeling study - Tianshan Shi; Xin Zhao; Xiaoshu Zhang; Lei Meng; Donghua Li; Xinfeng Liu; Hongmiao Zheng; Deshan Yu; Tingrong Wang; Rui Li; Juansheng Li; Xiping Shen; et al. (Archives of Virology, 2023)

Formulation improvement of a concentrated enzyme detergent for high-speed rail trains through life cycle assessment methodology - Changyan Yang; Yu Gong; Yinhang Qu; Jiayi Li; Bohan Yang; Rui Li; Dorothy S. Zhang; Baowei Wang; Yigang Ding; Bo Zhang (Environment, Development and Sustainability, 2023)

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

Exposure to cadmium induced gut antibiotic resistance genes (ARGs) and microbiota alternations of Babylonia areolata - Wang Zhao; Qian Han; Rui Yang; Weigeng Wen; Zhenghua Deng; Huan Li; Zhongming Zheng; Zhenhua Ma; Gang Yu (Science of The Total Environment, 2023)

Comprehensive analysis of the fates and risks of veterinary antibiotics in a small ecosystem comprising a pig farm and its surroundings in Northeast China - Jian-yong Wu; Jun-min Gao; Jin-song Guo; Xian-yu Hou; De-rui Wang; Jing-cheng Wu; Xiao-jun Li; Chun-yun Jia (Journal of Hazardous Materials, 2023)

Screening of hazardous groundwater pollutants responsible for microbial ecological consequences by integrated nontargeted analysis and high-throughput sequencing technologies - Jian Li; Shihang Yu; Quanzhen Liu; Donghong Wang; Lei Yang; Jinsheng Wang; Rui Zuo (Journal of Hazardous Materials, 2023)

Machine learning approaches to predict the apparent rate constants for aqueous organic compounds by ferrate - Shan-Shan Zheng; Wan-Qian Guo; Hao Lu; Qi-Shi Si; Bang-Hai Liu; Hua-Zhe Wang; Qi Zhao; Wen-Rui Jia; Tai-Ping Yu (Journal of Environmental Management, 2023)

Variability of fuel consumption and CO2 emissions of a gasoline passenger car under multiple in-laboratory and on-road testing conditions - Boya Zhou; Liqiang He; Shijian Zhang; Rui Wang; Luowei Zhang; Mengliang Li; Yu Liu; Shaojun Zhang; Ye Wu; Jiming Hao (Journal of Environmental Sciences, 2023)

Spatially dual-confined metallic selenide double active centers for boosting potassium ion storage - Juan Gong; Rui Zhang; Xijun Wei; Yu Liu; Qing Luo; Qi Wan; Qiaoji Zheng; Lei Wang; Shude Liu; Dunmin Lin (Chemical Engineering Journal, 2023)

Highly sensitive surface-enhanced Raman scattering (SERS) imaging for phenotypic diagnosis and therapeutic evaluation of breast cancer - Chonggui Qiu; Wei Zhang; Yanhong Zhou; Hongwang Cui; Yanlong Xing; Fabiao Yu; Rui Wang (Chemical Engineering Journal, 2023)

High density mapping of wheat stripe rust resistance gene QYrXN3517-1BL using QTL mapping, BSE-Seq and candidate gene analysis - Shuo Huang; Yibo Zhang; Hui Ren; Xin Zhang; Rui Yu; Shengjie Liu; Qingdong Zeng; Qilin Wang; Fengping Yuan; Ravi P. Singh; Sridhar Bhavani; Jianhui Wu; et al. (Theoretical and Applied Genetics, 2023)

The circadian regulation of extracellular ATP - Xin Wang; Yu-Ting Dong; Xiu-Ming Hu; Ji-Zhou Zhang; Nan-Rui Shi; Yan-Qin Zuo; Xu Wang (Purinergic Signalling, 2023)
Extracellular ATP is a potent signaling molecule released from various cells throughout the body and is intimately involved in the pathophysiological functions of the nervous system and immune system by activating P2 purinergic receptors. Recent increasingly studies showed that extracellular ATP exhibits circadian oscillation with an approximately 24-h periodicity, which participates in regulatory pathways of central oscillator suprachiasmatic nucleus and peripheral oscillator bladder, respectively. Oscillators modulate the protein expression of ATP release channels and ectonucleotidase activity through clock genes; indeed, real-time alterations of ATP release and degradation determine outcomes of temporal character on extracellular ATP rhythm. The regulatory pathways on extracellular ATP rhythm are different in central and peripheral systems. In this review, we summarize the circadian rhythm of extracellular ATP and discuss several circadian regulatory pathways in different organs via ATP release and degradation, to provide a new understanding for purinergic signaling in the regulatory mechanism of circadian rhythm and a potential target to research the circadian regulation of extracellular ATP in other circadian oscillators.

Individual tree segmentation and biomass estimation based on UAV Digital aerial photograph - Zhao Sun; Yi-fu Wang; Zhi-dan Ding; Rui-ting Liang; Yun-hong Xie; Rui Li; Hao-wei Li; Lei Pan; Yu-jun Sun (Journal of Mountain Science, 2023)

SLP-2 regulates the generation of reactive oxygen species and the ERK pathway to promote papillary thyroid carcinoma motility and angiogenesis - Jianping Chen; Duting Wang; Rui Xu; Ting Yao; Yu Guo; Qi Liu; Erlong Yang; Zhengqing Wu; Zhenyu Xu (Tissue and Cell, 2023)

Microbial-induced calcium carbonate precipitation: Influencing factors, nucleation pathways, and application in waste water remediation - Yu Liu; Amjad Ali; Jun-Feng Su; Kai Li; Rui-Zhu Hu; Zhao Wang (Science of The Total Environment, 2023)

Investigation on energy-saving extractive distillation for recovering ethanol and 1,4-dioxane from wastewater - Qingqing Rui; Qing Ye; Jinlong Li; Yao Wang; Azhi Yu (Process Safety and Environmental Protection, 2023)

Marine osmium‑uranium‑sulfur isotope evidence for the interaction of volcanism and ocean anoxia during the Middle Pleistocene in the tropical Western Pacific - Wenlong Pei; Jiayue Wang; Xinling Wang; Rui Zhang; Tiegang Li; Fan Zhang; Xiaoxiao Yu; Zhiyong Liu; Minglei Guan; Qi Han (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Tectono-sedimentary evolution of the Paleogene Qikou Sag, Bohai Bay Basin, NE China - Si Chen; Rui Zhao; Changwei Chen; Hua Wang; Jianghao Ma; Tianhao Gong; Zhenghong Yu (Marine and Petroleum Geology, 2023)

Ultrasensitive hydrogel grating detector for real-time continuous-flow detection of trace threat Pb2+ - Xiao-Yu Tian; Meng-Wei Sun; Guo-Yu Wen; Min Cao; Da-Wei Pan; Rui Xie; Xiao-Jie Ju; Zhuang Liu; Wei Wang; Liang-Yin Chu (Journal of Hazardous Materials, 2023)

Antimicrobial activity and mechanism of preservatives against Alicyclobacillus acidoterrestris and its application in apple juice - Zhouli Wang; Yu Tian; Qi Wang; Tianmin Guo; Yahong Yuan; Tianli Yue; Hang Jia; Qian Ge; Zidan Zhao; Rui Cai (International Journal of Food Microbiology, 2023)

Multiple strategies for high-efficiency expression of Thermomyces lanuginosus lipase in Pichia pastoris and production of biodiesel in solvent-free system - Rui Xu; Zirong Chen; Yanyang Chen; Xiaoyue Wang; Yu Zhang; Xun Li; Fei Wang (Fuel, 2023)

Consolidating the gelling performance of myofibrillar protein using a novel OSA-modified-starch-stabilized Pickering emulsion filler: Effect of starches with distinct crystalline types - Qingling Wang; Yi Luan; Ziwei Tang; Zhikun Li; Chen Gu; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Research International, 2023)

Metagenomic insights into bacterial communities and functional genes associated with texture characteristics of Kazakh artisanal fermented milk Ayran in Xinjiang, China - Malina Kuerman; Rui Wang; Yu Zhou; Xiaoying Tian; Qingyu Cui; Huaxi Yi; Pimin Gong; Zhe Zhang; Kai Lin; Tongjie Liu; Lanwei Zhang (Food Research International, 2023)

Friction induced mechanochemistry: self-adaptive lubrication through in-situ tribo-click system - Rui Dong; Yunlei Zhang; Hao-Zhe Xu; Luyao Bao; Shuanhong Ma; Xin-Gang Wang; Qiangliang Yu; Meirong Cai; Feng Zhou; Weimin Liu (Chemical Engineering Journal, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

MicroRNA-588 regulates the invasive, migratory and vasculogenic mimicry-forming abilities of hypoxic glioma cells by targeting ROBO1 - Rui Yu; Rongrong Zhao; Xiaopeng Sun; Zongpu Zhang; Shaobo Wang; Xiao Gao; Zhongzheng Sun; Hao Xue; Gang Li (Molecular Biology Reports, 2023)
Background The microenvironment of hypoxia is an important factor contributing to the development of glioblastoma (GBM). MicroRNA-588 and its potential target Roundabout-directed receptor 1 (ROBO1) have been reported to promote tumor invasion and proliferation in diseases such as gastric, pancreatic and hepatocellular carcinoma, while their function in GBM and response to hypoxic states remain elusive. Methods A microarray was leveraged to identify differentially expressed microRNAs in U251 glioma cells cultured under normoxic and hypoxic conditions. The expression of miR-588 was assessed using quantitative real-time PCR (qRT‒PCR). Gain- and loss-of-function studies were used to evaluate the role of miR-588 under hypoxic and normoxic conditions. Cell invasion, migration, proliferation, and vasculogenic mimicry (VM) formation experiments were performed. The relationship between miR-588 and ROBO1 was confirmed using western blot and luciferase reporter assays. Intracranial xenograft tumor mouse models were used to study the function of miR-588 in vivo. Results The expression of miR-588 was significantly upregulated in hypoxic glioma cells relative to normoxic glioma cells. miR-588 inhibited the invasive, migratory and VM-forming abilities of glioma cells in vitro and in vivo. Mechanistically, roundabout guidance receptor 1 (ROBO1) is a direct, functionally relevant target of miR-588 in glioma. ROBO1 knockdown suppressed the expression of matrix metallopeptidase 2 (MMP2) and matrix metallopeptidase 9 (MMP9), thereby inhibiting the invasive, migratory and VM-forming abilities of glioma. Conclusions MiR-588 regulated the behaviors of hypoxic glioma cells by targeting ROBO1. miR-588 can be used as a prognostic marker for glioma and has potential implications in glioma gene therapy.

TREM2 and Microglia Contribute to the Synaptic Plasticity: from Physiology to Pathology - Chao-Ji Yu; Meng Wang; Rui-Yang Li; Tao Wei; Han-Chen Yang; Yun-Si Yin; Ying-Xin Mi; Qi Qin; Yi Tang (Molecular Neurobiology, 2023)

Paenibacillus alkalitolerans sp. nov., a bacterium isolated from a salt lake of Turpan City in Xinjiang Province, north-west China - Rui Li; Zhou-Tian-Le Zhang; Yun Wang; Gang-Qiang Jiang; Min Yin; Yu Li; Wen-Yong Zhu; Shu-Kun Tang (Folia Microbiologica, 2023)

Effects of bepridil on early cardiac development of zebrafish - Ya-Lan Wei; Yu-Qing Lei; Zhou-Jie Ye; Xu-Dong Zhuang; Li-Ping Zhu; Xin-Rui Wang; Hua Cao (Cell and Tissue Research, 2023)

Intercrop overyielding weakened by high inputs: Global meta-analysis with experimental validation - Shuang-Guo Zhu; Hao Zhu; Rui Zhou; Wei Zhang; Wei Wang; Yi-Ning Zhou; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; Hong-Yan Tao; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2023)

The Impacts of Dietary Curcumin on Innate Immune Responses and Antioxidant Status in Greater Amberjack (Seriola dumerili) under Ammonia Stress - Chuanpeng Zhou; Zhong Huang; Shengjie Zhou; Jing Hu; Rui Yang; Jun Wang; Yun Wang; Wei Yu; Heizhao Lin; Zhenhua Ma (Journal of Marine Science and Engineering, 2023)
In this study, we investigated the effect of dietary curcumin on non-specific immune responses and antioxidative ability in Seriola dumerili under ammonia stress and post-recovery. Three diets were prepared to contain 0, 75, and 150 mg/kg of curcumin. A total of 225 greater amberjack (initial weight: 100.90 ± 0.03 g) were distributed into nine cylindrical tanks, constituting an experimental design with three treatments and three replicates. After 56 days of feeding, plasma, intestinal, and hepatic enzyme activities were evaluated. Then, an acute ammonia challenge experiment was conducted. Ten fish per tank were subjected to acute ammonia stress (total ammonia-N: 1000 mg/L) for eight minutes followed by six minutes of recovery. The results indicated that dietary curcumin significantly promoted intestinal and hepatic alkaline phosphatase (ALP) and acid phosphatase (ACP) levels as well as hepatic antioxidative enzymes such as superoxide dismutase (SOD), total antioxidant capacity (T-AOC), reduced glutathione (GSH), and glutathione peroxidase (GSH-Px) of greater amberjack. In addition, curcumin addition improved the activities of antioxidant enzymes, such as SOD, T-AOC, GSH, GSH-Px, and catalase (CAT), and reduced malondialdehyde (MDA) content in liver, spleen, head kidney, and brain tissues after post-recovery. The indexes related to immunity and antioxidant enzymes in the liver, gill, and spleen rose again to some extent, but they showed the worst recovery ability in the head kidney and brain tissue samples. These results indicate that dietary curcumin supplementation could increase non-specific immune responses, antioxidant ability, and enhance resistance to high ammonia stress in juvenile S. dumerili.

Unique bacterial communities and lifestyles in deep ocean blue holes: Insights from the Yongle Blue Hole (South China Sea) - Shun Zhou; Jiwen Liu; Peng Yao; Liang Fu; Zuosheng Yang; Yulin Zhang; Rui Du; Chao Jia; Lin Chen; Jinchang Liang; Xiaolei Wang; Xiaochong Shi; et al. (Frontiers in Marine Science, 2023)
Deep ocean blue holes possess steep physicochemical gradients, especially low dissolved oxygen concentration, which shape the extraordinary microbial communities. However, the environmental responses of microorganisms with different lifestyles and knowledge of culturable microorganisms in the blue holes are still unknown. Here, we investigated the bacterial community structure with different lifestyles of the world’s deepest blue hole - the Yongle Blue Hole (YBH) in the South China Sea using both culture-dependent and -independent methods. YBH can be divided by oxygen content into an oxic zone, a suboxic zone and two anoxic zones. The abundance of bacteria, archaea, genes dsrB and soxB were all higher in the free-living (FL) lifestyle than in the particle-associated (PA) lifestyle, yet the diversity and richness of PA bacteria were higher than that of FL bacteria. More Gammaproteobacteria and less Alphaproteobacteria , Chloroflexi and Nitrospinae were observed within the FL fraction than within the PA fraction. The relative abundance of sulfur-oxidizing bacteria (SOB) was dominant between 100-140 m (anoxic zone I) in YBH, with a maximum of 90.0% (140 m FL fraction). The SOB in YBH were mainly colorless sulfur bacteria and purple non-sulfur bacteria, of which Thiomicrorhabdus and Sulfurimonas were the main representatives. In addition, a total of 294 bacterial strains were isolated on a variety of media and culture conditions, and 22.2% (18/81) of anaerobic strains were identified as potential novel species. Our study reveals a distinction between FL and PA bacteria in YBH. It contributes to further understanding of the bacterial community in deep ocean blue holes, and provides bacterial resources for subsequent studies on their adaptation to extreme marine environments.

Evaluation of the pathogenesis of non-typical strain with α-hemolysin, Vibrio parahaemolyticus 353, isolated from Chinese seafood through comparative genome and transcriptome analysis - Fei Zha; Rui Pang; Shixuan Huang; Jumei Zhang; Juan Wang; Moutong Chen; Liang Xue; Qinghua Ye; Shi Wu; Meiyan Yang; Qihui Gu; Yu Ding; et al. (Marine Pollution Bulletin, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Secondary organic aerosol formation in China from urban-lifestyle sources: Vehicle exhaust and cooking emission - Zirui Zhang; Wenfei Zhu; Min Hu; Hui Wang; Lizi Tang; Shuya Hu; Ruizhe Shen; Ying Yu; Kai Song; Rui Tan; Zheng Chen; Shiyi Chen; et al. (Science of The Total Environment, 2023)

Analytical solutions on non-Darcy seepage of grouted and lined subsea tunnels under dynamic water levels - Xiang Liu; Dongchi Wang; Yu Zhang; Annan Jiang; Qian Fang; Rui Zhang (Ocean Engineering, 2023)

A stack-up electrochemical device based on metal-organic framework modified carbon paper for ultra-trace lead and cadmium ions detection - Yue-Hong Pang; Qiu-Yu Yang; Rui Jiang; Yi-Ying Wang; Xiao-Fang Shen (Food Chemistry, 2023)

Development of a recombinant adenovirus-vectored vaccine against both infectious hematopoietic necrosis virus and infectious pancreatic necrosis virus in rainbow trout (Oncorhynchus mykiss) - Shouhu Li; Xincang Li; Rui Yuan; Xiaoxue Chen; Shouxu Chen; Yu Qiu; Qingfeng Yang; Meng Wang; Jiangao Shi; Shuo Zhang (Fish & Shellfish Immunology, 2023)

Overlooked mechanism of Pb immobilization on montmorillonite mediated by dissolved organic matter in manure compost - Yuanchen Zhu; Qingkai Guan; Linghui Kong; Rui Yang; Wei Wang; Yu Jin; Xuesheng Liu; Juanjuan Qu (Environmental Pollution, 2023)

Breast adipose metabolites mediates the association of tetrabromobisphenol a with breast cancer: A case-control study in Chinese population - Ai Zhang; Rui Wang; Qianfeng Liu; Zhengjun Yang; Xiaohui Lin; Jing Pang; Xiaoyu Li; Dan Wang; Jiayu He; Jianping Li; Mingyue Zhang; Yue Yu; et al. (Environmental Pollution, 2023)

Ecological risk assessment based on soil adsorption capacity for heavy metals in Taihu basin, China - Feier Wang; Fuxin Wang; Hongrui Yang; Jie Yu; Rui Ni (Environmental Pollution, 2023)

Correlation analysis and modeling of human thermal sensation with multiple physiological markers: An experimental study - Kangji Li; Rui Yu; Yufei Liu; Junqiang Wang; Wenping Xue (Energy and Buildings, 2023)

Permanent displacement reliability analysis of soil slopes subjected to mainshock-aftershock sequences - Gan Wang; Rui Pang; Xiang Yu; Bin Xu (Computers and Geotechnics, 2023)

Balance the rapid release of insecticide microcapsules using double-layer shielding effect when the foliar application - Rui Wang; Song Liu; Feng-shou Sun; Xin Yu; Xiao Liu; Bei-xing Li; Wei Mu; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2023)

Temperature-gradient-induced enhanced fog collection on polymer brush surfaces - Zheng-Hong Liang; Rui Feng; Jia-Min Wu; Dong Li; Fang Wang; Xiu-Li Wang; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2023)

Functionally decorated metal–organic frameworks in environmental remediation - Yu Zhang; Bingquan Wang; Rui Wang (Chemical Engineering Journal, 2023)

Multifunctional lysosome-targetable fluorescent probe for imaging peroxynitrite in acute liver injury model - Kai Wang; Rui Guo; Xu-Yang Chen; Yu-Shun Yang; Lu-Qin Qiao; Ming-Lin Wang (Chemical Engineering Journal, 2023)

All-in-one additive enables defect passivated, crystallization modulated and moisture resisted perovskite films toward efficient solar cells - Chuanming Tian; Yu Zhao; Xuefei Han; Bin Li; Yichuan Rui; Hao Xiong; Yu Qiu; Wei An; Kerui Li; Chengyi Hou; Yaogang Li; Hongzhi Wang; et al. (Chemical Engineering Journal, 2023)

A High-efficiency blue-LED-excitable NIR-II-emitting MgO:Cr3+,Ni2+ phosphor for future broadband light source toward multifunctional NIR spectroscopy applications - Bo-Mei Liu; Xiao-Xuan Guo; Lu-Yu Cao; Lin Huang; Rui Zou; Zhi Zhou; Jing Wang (Chemical Engineering Journal, 2023)

Microfluidic emulsification techniques for controllable emulsion production and functional microparticle synthesis - Wei Wang; Bing-Yu Li; Mao-Jie Zhang; Yao-Yao Su; Da-Wei Pan; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Yousef Faraj; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

Interfacial modulation of organic-inorganic two-dimensional superlattices for efficient electromagnetic wave absorption - Wenjian Wang; Ke Ran; Xingwang Hou; Yilin Huang; Zidong Zhang; Dongxu He; Yuan Fang; Shuai Wang; Yu Liu; Rui Zhao; Xiao-Yu Yang; Weidong Xue (Chemical Engineering Journal, 2023)

Enhancing structural and cycle stability of Prussian blue cathode materials for calcium-ion batteries by introducing divalent Fe - Chong-Yu Du; Zi-Hao Zhang; Xun-Lu Li; Rui-Jie Luo; Cui Ma; Jian Bao; Jie Zeng; Xuan Xu; Fei Wang; Yong-Ning Zhou (Chemical Engineering Journal, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

Phytochemical and underlying mechanism of Mikania micrantha Kunth on antibiotic resistance genes, and pathogenic microbes during chicken manure composting - Yousif Abdelrahman Yousif Abdellah; Yu-Sen Luo; Shan-Shan Sun; Xi Yang; Hong-Yi Ji; Rui-Long Wang (Bioresource Technology, 2023)

Water-soluble brown carbon in PM2.5 at two typical sites in Guanzhong Basin: Optical properties, sources, and implications - Xiaofei Li; Feng Yu; Yiying Song; Chao Zhang; Fangping Yan; Zhaofu Hu; Yali Lei; Lekhendra Tripathee; Rui Zhang; Jingning Guo; Yuqin Wang; Qingcai Chen; et al. (Atmospheric Research, 2023)

Positional cloning identified HvTUBULIN8 as the candidate gene for round lateral spikelet (RLS) in barley (Hordeum vulgare L.) - Dandan Qin; Gang Liu; Rui Liu; Chunchao Wang; Fuchao Xu; Qing Xu; Yu Ling; Guoqing Dong; Yanchun Peng; Shuangtao Ge; Ganggang Guo; Jing Dong; et al. (Theoretical and Applied Genetics, 2023)
Key message Map-based cloning, subcellular localization, virus-induced-gene-silencing and transcriptomic analysis reveal HvTUB8 as a candidate gene with pleiotropic effects on barley spike and leaf development via ethylene and chlorophyll metabolism. Abstract Barley lateral spikelet morphology and grain shape play key roles in grain physical quality and yield. Several genes and QTLs for these traits have been cloned or fine mapped previously. Here, we report the phenotypic and genotypic analysis of a barley mutant with round lateral spikelet (rls) from cv. Edamai 934. rls had round lateral spikelet, short but round grain, shortened awn, thick glume and dark green leaves. Histocytologic and ultrastructural analysis revealed that the difference of grain shape of rls was caused by change of cell arrangement in glume, and the dark leaf color resulted from enlarged chloroplast. HvTUBULIN8 ( HvTUB8 ) was identified as the candidate gene for rls by combination of RNA-Seq, map-based-cloning, virus-induced-gene-silencing (VIGS) and protein subcellular location. A single G-A substitution at the third exon of HvTUB8 resulted in change of Cysteine 354 to tyrosine. Furthermore, the mutant isoform Hvtub8 could be detected in both nucleus and cytoplasm, whereas the wild-type protein was only in cytoplasm and granular organelles of wheat protoplasts. Being consistent with the rare phenotype, the “A” allele of HvTUB8 was only detected in rls , but not in a worldwide barley germplasm panel with 400 accessions. VIGS confirmed that HvTUB8 was essential to maintain spike integrity. RNA-Seq results suggested that HvTUB8 may control spike morphogenesis via ethylene homeostasis and signaling, and control leaf color through chlorophyll metabolism. Collectively, our results support HvTUB8 as a candidate gene for barley spike and leaf morphology and provide insight of a novel mechanism of it in barley development.

Soil water and phosphorus availability determines plant-plant facilitation in maize-grass pea intercropping system - Shuang-Guo Zhu; Hao Zhu; Zheng-Guo Cheng; Rui Zhou; Yu-Miao Yang; Jing Wang; Wei Wang; Bao-Zhong Wang; Hong-Yan Tao; You-Cai Xiong (Plant and Soil, 2023)

Clinical Decision on Disorders of Consciousness After Acquired Brain Injury: Stepping Forward - Rui-Zhe Zheng; Zeng-Xin Qi; Zhe Wang; Ze-Yu Xu; Xue-Hai Wu; Ying Mao (Neuroscience Bulletin, 2023)

Long-term effects of cattle manure application on the soil aggregate stability of salt-affected soil on the Songnen Plain of North-Eastern China - Shuo Zhao; Fei Yu; Cheyu Zhai; Rui Zhong; Ying Zhao; Yong Wang; Juan Zhang; Qingfeng Meng (Journal of Soils and Sediments, 2023)

Occurrence, correlation, and partitioning of organophosphate esters in soil and tree bark from a megacity, Western China - Can Wang; Rui-Yu Yuan; Shi-Qiang Wei; Ming-Jing He (Environmental Science and Pollution Research, 2023)

Selenite Ameliorates Cadmium-induced Cytotoxicity Through Downregulation of ROS Levels and Upregulation of Selenoprotein Thioredoxin Reductase 1 in SH-SY5Y Cells - Hecheng Wang; Shibo Sun; Yan Ren; Rui Yang; Jianli Guo; Yu Zong; Qiuxian Zhang; Jing Zhao; Wei Zhang; Weiping Xu; Shui Guan; Jianqiang Xu (Biological Trace Element Research, 2023)

Evaluating the effects of contact time and leaching solution on measured solubilities of aerosol trace metals - Rui Li; Shuwei Dong; Chengpeng Huang; Feng Yu; Fu Wang; Xiaofei Li; Huanhuan Zhang; Yan Ren; Mingxian Guo; Qingcai Chen; Baozhu Ge; Mingjin Tang (Applied Geochemistry, 2023)

Influence mechanism of the non-uniform inflow on performance of reactor coolant pump - Yu Song; Song Huang; Rui Xu; Zhengchuan Zhang; Junlian Yin; Dezhong Wang (Annals of Nuclear Energy, 2023)

The influence of hapten spacer arm length on antibody response and immunoassay development - Yuchen Bai; Rui Liu; Leina Dou; Weilin Wu; Wenbo Yu; Kai Wen; Xuezhi Yu; Jianzhong Shen; Zhanhui Wang (Analytica Chimica Acta, 2023)